2022
DOI: 10.1038/s41598-022-12727-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and breadth of antibody cross-reactivity induced by recombinant influenza hemagglutinin trimer vaccine is enhanced by combination adjuvants

Abstract: The effects of adjuvants for increasing the immunogenicity of influenza vaccines are well known. However, the effect of adjuvants on increasing the breadth of cross-reactivity is less well understood. In this study we have performed a systematic screen of different toll-like receptor (TLR) agonists, with and without a squalene-in-water emulsion on the immunogenicity of a recombinant trimerized hemagglutinin (HA) vaccine in mice after single-dose administration. Antibody (Ab) cross-reactivity for other variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…Although HA trimers may present quaternary epitopes not found in monomers and thereby elicit antibodies from a broader repertoire of B cell clones, , we aim to construct H1–E2 using HA monomers to facilitate synthesis, which is an important consideration for future nanoparticle vaccine scale-up. Moreover, we have also published IgG cross-reactivity profiles against different drift variants for mice that were administered monomeric or trimeric H5; we found that these datasets are highly correlated ( R 2 = 0.92), suggesting the immunogenicity of monomeric HA is broadly overlapping with trimeric HA …”
Section: Results and Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Although HA trimers may present quaternary epitopes not found in monomers and thereby elicit antibodies from a broader repertoire of B cell clones, , we aim to construct H1–E2 using HA monomers to facilitate synthesis, which is an important consideration for future nanoparticle vaccine scale-up. Moreover, we have also published IgG cross-reactivity profiles against different drift variants for mice that were administered monomeric or trimeric H5; we found that these datasets are highly correlated ( R 2 = 0.92), suggesting the immunogenicity of monomeric HA is broadly overlapping with trimeric HA …”
Section: Results and Discussionmentioning
confidence: 82%
“…Moreover, we have also published IgG cross-reactivity profiles against different drift variants for mice that were administered monomeric or trimeric H5; we found that these datasets are highly correlated ( R 2 = 0.92), suggesting the immunogenicity of monomeric HA is broadly overlapping with trimeric HA. 78 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the COBRA HA antigens were formulated with AddaVax TM , a squalene-based MF-59-like adjuvant [ 52 , 53 ]. This adjuvant induces predominantly Th2-type humoral responses, preferentially stimulates CD4+ T cells to help B cell differentiation into IgG1-secreting cells in the presence of IL-4 and other anti-inflammatory cytokines by attracting more immune cells to site of injection, and upregulates antigen trafficking and presentation [ 54 , 55 ]. Intranasal infection with influenza viruses results in a more Th1-biased immune response, as observed in pre-immune, but mock-vaccinated mice ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%